2022
DOI: 10.1111/1440-1630.12806
|View full text |Cite
|
Sign up to set email alerts
|

Daily living skills of autistic adolescents and young adults: A scoping review

Abstract: Introduction Daily living skills (DLS) are essential for an increased quality of life and autonomous living. DLS are a focus of occupational therapy practice; however, there has been no identified review of DLS acquisition in autistic adolescents or adults. A scoping review was undertaken of which the objective was to evaluate and synthesise the extent, range, and nature of research activity, and to identify research gaps in the existing literature as they relate to DLS acquisition and autistic adolescents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…How care and social interventions are planned is especially important for individuals with autism and are a prerequisite for engagement in occupations. Auld et al showed in their review that the performance of everyday occupations was of importance to improve an individual's quality of life and well‐being (Auld et al, 2022). The findings from the present study showed that the regular daily schedule, including rules and psychological safety, provided by the supervisors enabled calmness and the emergence of a wider comfort zone, which had previously only encompassed the home but now included the farm, the animals, and the peer group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How care and social interventions are planned is especially important for individuals with autism and are a prerequisite for engagement in occupations. Auld et al showed in their review that the performance of everyday occupations was of importance to improve an individual's quality of life and well‐being (Auld et al, 2022). The findings from the present study showed that the regular daily schedule, including rules and psychological safety, provided by the supervisors enabled calmness and the emergence of a wider comfort zone, which had previously only encompassed the home but now included the farm, the animals, and the peer group.…”
Section: Discussionmentioning
confidence: 99%
“…People with autism (Socialstyrelsen, 2017(Socialstyrelsen, , 2019a) may have difficulties in communicating and socialising with others, as well as changing from one activity to another (APA, 2013;WHO, 2023). This may lead to problems in developing skills in everyday life (Auld et al, 2022) and to social withdrawal (Teo et al, 2015), that is, avoiding activities and meetings with people outside home. Animals can possibly contribute to cognitive and socioemotional learning for people with autism, which is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…However, the transition to independence can be difficult for those with ASD, because daily living skills (i.e., adaptive behaviors) are particularly problematic in ASD. Daily living skills may improve from childhood to adolescence in ASD ( Bal et al, 2015 ), but seem to plateau during adolescence and early adulthood in ASD ( Clarke et al, 2021 ; Auld et al, 2022 ; but see Smith et al, 2012 for later plateau in adulthood). Daily living skills and executive function (EF) in ASD are worse than expected on the basis of IQ, and the gap between these skills and IQ increases from adolescence into adulthood ( Rosenthal et al, 2013 ; Pugliese et al, 2015 ; Kraper et al, 2017 ; Tillmann et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…42 However, this research has mostly been based on parent reports, or focused on providing training for ADL skills development, with minimal research asking autistic people themselves about their needs or experiences. 43 A recent study asked older autistic adults about their IADLs, highlighting that these were impacted not only by individual factors, such as sensory sensitivity and executive function, but also influenced by environmental and cultural factors. 44 There is no research to date that seeks to understand the impact of managing these daily living skills on health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%